Investment Risk Tolerance amongst South African University Students in the Vaal Triangle Area - Evangelou, Antonios; Ferreira-Schenk, Sune; Ferreira, Lorainne; Bothma, Elizabeth (International Journal of Economics and Financial Issues, 2022)
Analysing students risk tolerance during the investor life cycle is imperative to students and financial planners alike, to facilitate the implementation of suitable investments and investment strategies. Students in universities do not have the required knowledge to invest and this is why an investment framework was created to assist, guide and inform students of what stage of the individual investor life cycle that they are in and suggest suitable investment strategies. The article implemented a quantitative approach, using secondary data analysis. The data used for the analysis is from a self-administered questionnaire in 2017 that was distributed to a sample of 396 students from two higher education institutions in the Vaal Triangle region. Two validated risk tolerance scales were used to analyse students risk tolerance levels. The objective of this paper was to determine the risk tolerance levels of students in the Vaal Triangle region. The two results from the 13-item scale and the single-item scale for measuring risk tolerance indicated that the students have a medium risk tolerance level.